Physical and Biological Properties of a Chitosan Hydrogel Scaffold Associated to Photobiomodulation Therapy for Dental Pulp Regeneration: An In Vitro and In Vivo Study. (27th January 2021) - Moreira, Maria Stella; Sarra, Giovanna; Carvalho, Giovanna Lopes; Gonçalves, Flavia; Caballero-Flores, Hector Valentin; Pedroni, Ana Clara Fagundes; Lascala, Cesar Angelo; Catalani, Luiz Henrique; Marques, Márcia Martins
Abstract : Background . The regeneration of dental pulp, especially in cases of pulp death of immature teeth, is the goal of the regenerative endodontic procedures (REPs) that are based on tissue engineering principles, consisting of stem cells, growth factors, and scaffolds. Photobiomodulation therapy (PBMT) showed to improve dental pulp regeneration through cell homing approaches in preclinical studies and has been proposed as the fourth element of tissue engineering. However, when a blood clot was used as a scaffold in one of these previous studies, only 30% of success was achieved. The authors pointed out the instability of the blood clot as the regeneration shortcoming. Then, to circumvent this problem, a new scaffold was developed to be applied with the blood clot. The hypothesis of the present study was that an experimental injectable chitosan hydrogel would facilitate the three-dimensional spatial organization of endogenous stem cells in dental pulp regeneration with no interference on the positive influence of PBMT. Methods . For the in vitro analysis, stem cells from the apical papilla (SCAPs) were characterized by flow cytometry and applied in the chitosan scaffold for evaluating adhesion, migration, and proliferation. For the in vivo analysis, the chitosan scaffold was applied in a rodent orthotopic dental pulp regeneration model under the influence of PBMT (660 nm; power output of 20 mW, beam area of 0.028 cm 2, and energy density of 5 J/cm 2 ). Results . The scaffold tested in this study allowed significantly higher viability, proliferation, and migration of SCAPs in vitro when PBMT was applied, especially with the energy density of 5 J/cm 2 . These results were in consonance to those of the in vivo data, where pulp-like tissue formation was observed inside the root canal. Conclusion . Chitosan hydrogel when applied with a blood clot and PBMT could in the future improve previous results of dental pulp regeneration through cell homing approaches.